Ranking of Waste Management Options Under Conditions of Possibilistic Uncertainty Using Fuzzy SAW - Raymond Girard R. Tan (ASEAN Journal of Chemical Engineering, 2005)
Integrated waste management involves the use of appropriate techniques ranging from pollution prevention/cleaner production (P2/CP) to conventional end-of-pipe controls. Design or retrofit of process plants usually entails selection of an optimal waste management measure from a number of alternatives. The selection process involves consideration of multiple criteria and data uncertainty, the latter being arguably possibilistic (fuzzy) rather than probabilistic (random) in nature. A fuzzy simple additive weighting (SAW) algorithm is proposed for such problems and demonstrated on a case study. The principal feature of the techniques shown is the retention of fuzzy confidence levels during the assessment of different technological options. Keywords:Cleaner production, fuzzynumbers, pollutioncontrol, pollution prevention, and possibility theory.